A 12-year epidemiological study of Acinetobacter baumannii from blood culture isolates in a single tertiary-care hospital using polmerase chain reaction (PCR)–based open reading frame typing. Issue 1 (8th August 2022) - Fujikura, Yuji; Hamamoto, Takaaki; Yuki, Atsushi; Sampei, Ayumi; Ichie, Nozomi; Takamizawa, Kazuho; Nomura, Sakika; Serizawa, Yusuke; Ohno, Tomohiro; Tsujimoto, Hironori
Abstract: Objective: Acinetobacter baumannii is a causative agent of healthcare-associated infections, and the introduction and spread of A. baumannii that has acquired drug resistance within a hospital are serious healthcare problems. We investigated the transition of epidemic clones and the occurrence of outbreaks by molecular epidemiological analysis to understand the long-term behavior of A. baumannii within a single facility. Methods: A. baumannii isolates collected from blood-culture–positive patients between January 2009 and December 2020 were subjected to PCR-based open reading frame typing (POT) for species identification, clonal typing, and homology searches. Results: Of the strains isolated from blood cultures, 49 were identified as A. baumannii and analyzed with POT. The POT#1=122 clones had different antimicrobial resistance profiles to the other POT clones, and strains belonging to this clone were dominant during outbreaks of multidrug-resistant Acinetobacter . Although the clonal diversity of A. baumannii decreased and its antimicrobial resistance increased during the outbreaks, clonal diversity and the in-hospital antibiogram improved at the end of the outbreaks. The POT#1=122 clone was not eliminated from the hospital during the study period. Conclusions: POT is a simple and suitable method for molecular epidemiological monitoring and can show the introduction, outbreak, and subsequent transition of an epidemic clone of A. baumannii.